METHODOLOGY FOR THE USE OF ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS - Samiyeva Zuhra Ilhom qizi (International Journal of Literature and Language Studies, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed modern educational systems by introducing innovative approaches to teaching, learning, and educational management. This study examines the methodological framework for integrating Artificial Intelligence into the educational process and evaluates its pedagogical potential in improving instructional effectiveness and student learning outcomes. The research analyzes contemporary AI-based educational technologies, including adaptive learning systems, intelligent tutoring systems, generative AI tools, automated assessment platforms, and personalized learning environments. The study highlights the methodological principles required for effective AI implementation, emphasizing learner-centered instruction, competency-based education, digital literacy, and ethical AI use. The findings indicate that AI-supported methodologies enhance student engagement, academic performance, independent learning, and teachers’ instructional efficiency while reducing routine administrative tasks. Furthermore, the study discusses the challenges associated with AI adoption, including academic integrity, data privacy, algorithmic bias, and the necessity of continuous professional development for educators. The proposed methodological framework provides practical recommendations for the responsible integration of Artificial Intelligence into educational practice. The study concludes that AI should be considered a complementary educational technology that supports, rather than replaces, the professional role of teachers in creating effective, personalized, and innovative learning environments.